Persepsi pekerja terhadap budaya pembelajaran di sebuah syarikat pengeluaran simen di Kuching Sarawak - Liew, Siew Chang (Universiti Malaysia Sarawak, (UNIMAS), 1998)
The aim of this study is to determine the perception of employees toward learning culture in a cement manufacturing firm in Kuching, Sarawak. It studies the difference in perception among the employees toward learning culture based on socio-demographic characteristics, such as age, gender, qualification, position and working experiences. Besides, relationship between perception of employees toward learning culture with openness, learning from failures, learning from experimentation, reward, creativity and information system is also studied. The population of this study were all full time employees of the firm. A sample of 43 employees (5 executives and 38 non-executives) was randomly selected from the population. Questionnaire was used to obtain employee's feedback. It solicits personal information and contains 49 items of 5 points Likert scale. A total of 11 hypothesis were formed. One-way ANOV A was used to analyse the difference in perception of employees toward learning culture based on socio-demographic characteristic, such as age, qualification, position and working experience. Independent Samples t-Test was used to analyse the difference in perception of employees toward learning culture based on gender. Pearson correlation test was used to analyse the relationship between openness, learning from failures, learning from experiences, reward, creativity and information system with the perception of employees toward learning culture.The findings of the study showed that 72.1 percent of the employees' perceived the learning culture highly in the organisation. Besides, there is no significant difference in the perception of employees toward learning culture based on socio-demographic characteristic, such as age, gender, qualification, position and working experiences. The correlation between the perception of employees toward learning culture with openness, reward and creativity is found to be positive and significant. Openness, reward and creativity have moderate correlation with perception of employees toward learning culture, whereas there is no correlation between the perception of employees toward learning culture with learning from failures, learning form experimentation and information systems. The implication of these findings is that openness, reward and creativity are necessary for the development of learning culture in an organisation. Hence, they should be nurtured in order to enhance a pleasant learning culture in an organisation.